PENGARUH PEMBERIAN MAKANAN OLAHAN DAUN PEPAYA TERHADAP PENINGKATAN ASI DI PUSKESMAS LEGOK KECAMATAN LEGOK KABUPATEN TANGERANG - Margareta Margareta; Fazar Kumaladewi (Midwifery Science Care Journal, 2024)
Coverage of exclusive breastfeeding in Banten Province is still far from the expected national target. In Banten Province coverage of exclusive breastfeeding has only reached 67% of the target of 80%. One obstacle that occurs is a decrease in milk production owned by nursing mothers. Some studies show that the average milk production increases 5-7 times after consumption of papaya leaves. The aim of this study is to see the impact of consumption processed food papaya leaves to increase milk production in breastfeeding mothers. The study design is quasy experiment with a population of breastfeeding mothers aged 0-6 months with a sampling technique that is a total sampling of 15 intervention group mothers and 15 control group mothers. The analysis used is the paired t-test. The results of data analysis in the intervention group showed a p-value of 0.000, which means that the amount of ASI production before and after intervention is very significant. The results of data analysis between intervention and control groups also showed a p value of 0.001, meaning a significant difference in milk production between the intervention and control groups. The results of this study prove that papaya leaf processed food is proven to form groups of breast milk enthusiasts in places other than where the experiment so be able to increase milk production. With this research, it is expected to improve health and families who are able to encourage mothers to buy processed papaya leaves to increase milk production and increase consumption at the Legok Special Health Center and Banten Province.